"The Vapourings of Empty Young Men?": Legacies of their hostility between 1916 and 1918 in British newspaper treatment of conscientious objectors during the German blitzkrieg and invasion scare of 1940. (18th May 2016) - Luckhurst, Tim
Abstract : In both world wars, British governments depicted tolerance of conscientious objectors as an example of their respect for the principle of individual liberty and contrasted their stance with that of Britain's enemies. Simultaneously, ministers faced an urgent need to conscript manpower. These conflicting demands presented a dilemma for newspapers. Should they demonstrate editorial independence from state and majority opinion through balanced coverage of this most divisive issue, or should they act as cheerleaders for the patriotic cause? Part of a project to present case studies of newspaper treatment of significant political controversies during the Second World War, this paper considers the reporting and analysis of conscientious objection in a structured sample of British newspapers between Monday 16 May 1940 and Friday 14 June 1940. It seeks to establish the extent to which prejudices displayed during the First World War reappeared in journalism published during this most desperate period of the Second.